EDUCATIONAL ETHNOGRAPHY: SCHOOL LIFE PRACTICES AND THE FORMATION OF MULTICULTURAL IDENTITY AT SMP NEGERI 1 SUMBANG - Aisyah Puan Maharani; Ibnu Da’I Munis; Mita Tamaminni’mah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aimed to describe school-life practices that reflect multicultural values and to analyze the process of multicultural identity formation among students at SMP Negeri 1 Sumbang. Using a qualitative approach with a phenomenological method, the research explored the lived experiences of students, teachers, and other school actors through observation, interviews, and documentation. The findings showed that ethnic, religious, and socioeconomic diversity shaped an inclusive social environment within the school. Multicultural values were implicitly integrated into learning activities, particularly in Pancasila Education, Religious Education, and Indonesian Language classes, although they were not yet supported by a systematic curricular policy. Students' social interactions demonstrated ongoing identity negotiation through language, cultural symbols, and cross-group collaboration. Teachers played a significant role in fostering inclusive and dialogical pedagogy to prevent identity-based tension. This study concludes that multicultural identity formation is not an automatic process but emerges through continuous social experiences supported by a school culture that respects diversity.